2020
DOI: 10.7759/cureus.9886
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis in Mild COVID-19 Infection

Abstract: The novel coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has caused a global health crisis. This virus uses angiotensin converting enzyme 2 (ACE2) receptors to facilitate cellular entry. ACE2 receptors appear to be highly expressed in pancreatic exocrine glands and islet cells, more so than in lung tissues, suggesting that pancreatic injury can occur despite having only mild COVID-19 symptoms. We report a patient with COVID-19 who presented with only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 8 publications
2
19
1
Order By: Relevance
“…Gonzalo-Voltas et al 9 reported a case of pancreatitis from Spain in the absence of the most common risk factors: alcohol and gallstones. 9 Lakshmanan and Malik 10 also reported a case of a nursing home resident who tested positive for SARS-CoV-2 following an outbreak at his residence and developed pancreatitis a few days later. Moreover, Brikman et al 11 reported a case of a patient with COVID-19 pneumonia who developed acute pancreatitis 14 days following admission.…”
Section: Discussionmentioning
confidence: 99%
“…Gonzalo-Voltas et al 9 reported a case of pancreatitis from Spain in the absence of the most common risk factors: alcohol and gallstones. 9 Lakshmanan and Malik 10 also reported a case of a nursing home resident who tested positive for SARS-CoV-2 following an outbreak at his residence and developed pancreatitis a few days later. Moreover, Brikman et al 11 reported a case of a patient with COVID-19 pneumonia who developed acute pancreatitis 14 days following admission.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] Since the beginning of the pandemic, associations have been drawn between COVID-19 infection and pancreatic injury and pancreatitis. Case reports have detailed the development of clinical pancreatitis following COVID-19 infection, [46][47][48][49][50] and several studies have suggested that elevations in amylase and lipase may be a fairly common feature of infection. 51,52 As noted above in studies focused on the islet, data on whether ACE2 is enhanced or decreased in pancreatic exocrine cells are conflicting, with some datasets suggesting an increase in ACE2 expression in the exocrine pancreas 40,53,54 and others suggesting relative depletion among the exocrine cells.…”
Section: Effects On β Cells Due To Infection Of Surrounding Cellsmentioning
confidence: 99%
“…Lakshmanan et al [ 30 ] reported the case of a 68-year-old man with pneumonia and AP manifesting with nausea, vomiting, and anorexia, without abdominal pain, with increased amylase and lipase levels in laboratory results. Abdominal CT showed pancreatic and peripancreatic inflammation typical for AP.…”
Section: Case Reports and Cohort Studies On Ap In Covid-19 In The Literature Searchmentioning
confidence: 99%
“…Conservative treatment (intravenous fluids, analgesics, antibiotics, and antiemetics) was used. After 7 d of treatment, he was discharged in good clinical condition[ 30 ].…”
Section: Case Reports and Cohort Studies On Ap In Covid-19 In The Literature Searchmentioning
confidence: 99%